An Improved ZVT-ZCT PWM DC-DC Boost Converter With Increased Efficiency - Akin, Burak (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2014)
A new active snubber cell is proposed for a dc-dc boost converter. Zero voltage transition (ZVT) turn on and zero current transition (ZCT) turn off are provided by this active snubber cell. There is no extra current or voltage stresses on the main switch. Also, zero current switching (ZCS) turn on and ZCT turn off are provided for the auxiliary switch. Although there is no extra voltage stress on the auxiliary switch, a current stress is present. However, auxiliary switch current stress is decreased by coupling inductance. The coupling inductance transfers the part of the current stress to the output load according to the transform ratio. In this paper, the ZVT-ZCT PWM dc-dc boost converter's steady-state analysis is proposed for one switching cycle. Experimental application and theoretical analysis are proved by 300 W prototype with 100 kHz switching frequency. As a result, an improved ZVT-ZCT PWM boost converter reaches 98.7% total efficiency at full load with lowered current stress.
Keywords: Active snubber; zero current switching (ZCS); zero current transition (ZCT); zero voltage switching (ZVS); zero voltage transition (ZVT); Engineering